Predictors for regional lymph node metastasis in T1 rectal cancer: a population-based SEER analysis - Brunner, Walter; Widmann, Bernhard; Marti, Lukas; Tarantino, Ignazio; Schmied, Bruno; Warschkow, René (Surgical endoscopy and other interventional techniques, 2016)
Local resection of early-stage rectal cancer significantly reduces perioperative morbidity compared with radical resection. Identifying patients at risk of regional lymph node metastasis (LNM) is crucial for long-term survival after local resection.
Gesehen am 20.05.2020